Soil water retention curve and hydraulic soil in coffee crop conilon submitted to subsoiling - Souza, Joabe Martins de; Bonomo, Robson; Pires, Fábio Ribeiro; Bonomo, Diego Zancanella (Coffee Science - ISSN 1984-3909, 2014)
The objective of this study was to evaluate the effect of tillage, water retention and soil hydraulic conductivity in Conilon coffee crop (Coffea canephora Pierre) submitted to subsoiling in the row. The area of this experiment was comprised of three plots T11, T7 and T3, with coffee grown to 11 7 to 3 years respectively. Undisturbed samples were taken in the line (P1) and leading (P2), and layers 0.00-0.20, 0.20-0.40,0.40 0.60, 0.60-0.80 m, with three replicates for evaluation of water retention and hydraulic conductivity. The P1 in T11 showed higher water content at field capacity, as well as similar curves for all layers. The T7 showed higher water content retained in the P2 all voltages in layers of from 0.20 to 0.80 m, most P1 now available water-layer was 0.00 to 0.20 m, and the lower layer 0.60-0.80 m. In T3 greater retention in P1 was, in layers of 0.00 to 0.60 m, due to increased water retention in low voltages. Hydraulic conductivities statistics differ between the studied positions, layers of 0.00-0.20 and 0.20-0.40 were accepted me not between plots, with higher conductivity in the layers from 0.00 to 0.40 m. The subsoiling provided greater water retention at low voltages, increased the available water in the soil layer of 0.00 to 0.60 m, compared to the spacing, the soil hydraulic conductivity was increased and correlated negatively with microporosity and positively with total porosity and macroporosity, and the effect does not vary with time after soil tillage.